Thematic Study: Aims Of Education In The Prophetic Hadith - Suchi Nurul Khofifah; Fery Darmawan; Zulfahmi Lubis; Muhammad Nasrullah Ramadhana; Bintang Arif Samudra (Jurnal Multidisiplin Sahombu, 2024)
This article aiming For to expose about objective from education in hadiths Prophet Muhammad sallallaahu'alaihi wasallam . Which includes from hadiths related prophets​ with Education, and on the paper This writer also will to dig about criticism matan and rawi , explanation hadith , its application and conclusion . Islamic education is very important thing For discussed However A little research that focuses on excavation Educational goals of hadith . This paper use approach qualitative Library study with analyzing the data contained in the Hadiths on Education in hadiths prophet . The data in question is a number of related hadith​ with the goals of Islamic education taken from several books ( source ), then hadith the analyzed from aspect Contents hadith ( matan ) or narrator hadith . Based on Study This can produce A draft with the purpose of Islamic education , author get formulation objective Islamic education includes ; First , form and develop relation scientific . Second , servitude self to Allah SWT​ ta'aala . Third , get manifested goodness​ in forms charity pious . Fourth , direct life its implementation to afterlife ( ukhrawi ). Fifth , develop human nature in accordance with stages grow the flower in environment social .